2022
DOI: 10.3390/ijerph19063425
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Effects of Drought on Selected Causes of Mortality in Northern Bangladesh

Abstract: Drought has exacerbated morbidity and mortality worldwide. Here, a time series study was conducted in northern Bangladesh to evaluate the impact of drought on selected causes of mortality during 2007–2017. Rainfall and temperature data from six meteorological stations were used to analyze drought and non-drought periods and to categorize mild, moderate, severe, and extreme drought based on the 3-month and 12-month Standardized Precipitation Index (SPI) and Standardized Precipitation Evaporation Index (SPEI). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In line with our results, Salvador et al [22] suggested an indication of higher risks related to a longer accumulation period (SPEI3) compared to the shortest one (SPEI1) in peninsular Spain, especially for respiratory mortality. However, other studies suggested a higher negative influence on mortality risk in shorter droughts (3 months of accumulation) compared to longer droughts (12 months of accumulation) in northern Bangladesh [24,49]. Thus, further evidence is needed to clarify existing uncertainties.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…In line with our results, Salvador et al [22] suggested an indication of higher risks related to a longer accumulation period (SPEI3) compared to the shortest one (SPEI1) in peninsular Spain, especially for respiratory mortality. However, other studies suggested a higher negative influence on mortality risk in shorter droughts (3 months of accumulation) compared to longer droughts (12 months of accumulation) in northern Bangladesh [24,49]. Thus, further evidence is needed to clarify existing uncertainties.…”
Section: Discussionmentioning
confidence: 94%
“…more extended droughts). Different characterization of drought events, as well as the use of different drought indices, may also influence drought-related mortality [2,4,23,24]. Meanwhile, differences found in this study across district municipalities may be explained by potential differences in the drought exposure as well as in the adaptative capacity and resilience of the populations (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations